Learning Programming Using Objects-First Approach Through Folktales - Ling, Siew Woei; Imran Hazimin, Othman; Chuah, Kee Man (UTM Press, 2015)
Teaching programming to the amateur programmers and non-programmers with design and educational technology background are tough. Needless to say, it is pertinent for them to have some basic programming skills. We realized the needs to motivate the potential programmers therefore, proposed the integration of folktales in learning programming. This paper shares an approach of teaching programming using the folktales to create awareness also to simulate the amateur and non-programmers interested with folktales at the same time motivated to complete a creation of digital story using 3D programming software, Alice and Unity. Mixed-methods approach revealed participants’ positive behavior towards learning programming although it was perceived difficult. The finding also indicates that they can understand the programming language and successfully explored the software to create a digital story.